PERFORMANCE BASED PAY AS A DETERMINANT OF JOB SATISFACTION: A STUDY IN MALAYSIA GIATMARA CENTERS - Azman ISMAIL; Nurhana M RAFIUDDIN; Mohd Hamran MOHAMAD; Norashikin Sahol HAMID; Aniza WAMIN; Nurzawani ZAKARIA (Management & Marketing)
Compensation management literature highlights that performance based payhas two major characteristics: participation in pay systems and adequacy ofpay. The ability of management to properly implement such pay systems maylead to increased job satisfaction in organizations. Though, the nature of thisrelationship is interesting, little is known about the influence of performancebased pay on job satisfaction in compensation management literature.Therefore, this study was conducted to examine the relationship between payfor performance and job satisfaction in Malaysian GIATMARA centers. Theresults of exploratory factor analysis confirmed that measurement scalesused in this study satisfactorily met the standards of validity and reliabilityanalyses. An outcome of stepwise regression analysis shows thatdeterminant of job satisfaction is performance based pay. Further, this resultconfirms that pay for performance is an important antecedent for jobsatisfaction in the studied organizations.